A Preliminary Study of Yoga Tourism and its Prospects in Nepal - Kunwar, Ramesh R.; Sharma, Netra P. (Journal of APF Command and Staff College, 2020)
This article attempts to reveal the prospects of yoga tourism in Nepal. Yoga is gaining popularity worldwide due to its inherent quality to transform a person from illness to wellness. This is the reason yoga tourism is studied in academia under the umbrella term of wellness tourism. There are potentialities how Nepal can be one of the best destinations for yoga tourism. Nepal is spiritually saturated country being the birthplace of Gautama Buddha and playground of Lord Shiva, the Yogishwara. At the same time, Nepal is a Himalayan country including the highest mountain, Mt. Everest. The cultural heritage is another attraction. The simplicity of people attracts tourists who aim to learn yoga practices while visiting places for refreshment. This article has dealt about how yoga tourism is spreading, what are its theoretical and philosophical background, prospects and potentialities and so on. The major methodology applied in this article is library research, case studies and visiting actual places where yoga tourists from all over the world gather. Yoga retreat survey has revealed actual scenario of yoga tourism. Historicity of yoga philosophy is uncovered using original Classical Sanskrit Cannons. A sample survey identified yoga retreat centers in Kathmandu, the facilities available and potential aspects of tourism and income generation. The finding section documented the actual problems and prospects faced by the hosts, i.e., travel agencies, owners of yoga retreat centers, hoteliers, and yoga masters. The research has reached in conclusion: if right policies and facilities are generated, Nepal will gain a new identity as best destination for yoga tourism in the world. There are potentialities to develop internal yoga tourism as well. One can visualize Nepal being famous and prosperous from yoga tourism and Nepalese people gaining health, wealth and wellbeing by living yogic lifestyle and collecting reputation as yoga masters by guiding tourists into yoga life.